An estimation method for regional transport contributions from emission sources based on a high-mountain site: a case study in Zhumadian, China. (15th October 2021) - Huang, Haiyan; Liu, Baoshuang; Li, Sen; Choe, Tong-Hyok; Dai, Qili; Gu, Yao; Diao, Liuli; Zhang, Songfeng; Bi, Xiaohui; Luo, Zhongwei; Lu, Miaomiao; Zhang, Yufen; et al.
Abstract: The influence of near surface local emissions on the air quality at a high-mountain measurement site is generally extremely low. A novel approach was developed using observation from a high-mountain background site to quantitatively locate regional source contributions from different transport directions. Source contributions were apportioned by positive matrix factorization (PMF) and the air mass backward trajectories arrived at different times were calculated using the Hybrid Single-Particle Lagrangian Integrated Trajectory Model (HYSPLIT). The source contributions from different transport directions were estimated by coupling backward trajectories in different directions with different source contributions in terms of time. Combined the PMF results with potential source contribution function (PSCF)/concentration weighted trajectory (CWT) methods, the potential influence regions of multiple emission sources from different directions were located. The proposed method was applied to Baiyun Mountain in Zhumadian, China. Results show that the primary directions of regional transport were from the east and southeast by south in summer (Northern Anhui, Southern Henan, and Central and Mid-Northern Hubei Province). Contribution from the southeast by south direction was the largest regional source for secondary sulphate (15.53%) with the primary contributing regions being Western Anhui, Southeastern Henan, and Central Hubei. While in autumn, the main transport directions were from the southeast and northeast, with Mid-Eastern Henan, Southwestern and Southeastern Shandong, and Northern Anhui Province being the major contributing regions. Transport contributions for secondary nitrate and coal combustion were dominated from southeaster (24.34%) and northeaster (22.17%), where the potential contribution regions were located in Mid-Eastern Henan, Southwest Shandong, and Northern Anhui Province. Graphical abstract: Image 1 Highlights: A novel estimation method for regional transport contributions was developed. Transport contributions and potential areas from multiple directions were quantified. Secondary source transport contributions were highest in summer and autumn.